The Role of TLR4 on B Cell Activation and Anti-β2GPI Antibody Production in the Antiphospholipid Syndrome - Si Cheng; Haibo Wang; Hong Zhou (Journal of Immunology Research)
High titer of anti-β2-glycoprotein I antibodies (anti-β2GPI Ab) plays a pathogenic role in antiphospholipid syndrome (APS). Numerous studies have focused on the pathological mechanism in APS; however, little attention is paid to the immune mechanism of production of anti-β2GPI antibodies in APS. Our previous study demonstrated that Toll-like receptor 4 (TLR4) plays a vital role in the maturation of bone marrow-derived dendritic cells (BMDCs) from the mice immunized with human β2-glycoprotein I (β2GPI). TLR4 is required for the activation of B cells and the production of autoantibody in mice treated with β2GPI. However, TLR4 provides a third signal for B cell activation and then promotes B cells better receiving signals from both B cell antigen receptor (BCR) and CD40, thus promoting B cell activation, surface molecules expression, anti-β2GPI Ab production, and cytokines secretion and making B cell functioning like an antigen presenting cell (APC). At the same time, TLR4 also promotes B cells producing antibodies by upregulating the expression of B-cell activating factor (BAFF). In this paper, we aim to review the functions of TLR4 in B cell immune response and antibody production in autoimmune disease APS and try to find a new way for the prevention and treatment of APS.